Analysis of Typed Inclusion Dependencies with Null Values - Vladimir S. Zykin; Sergey V. Zykin (Моделирование и анализ информационных систем, 2017)
Null values have become an urgent problem since the creation of the relational data model. The impact of the uncertainty aﬀects all types of dependencies used in the design and operation of the database. This fully applies to the inclusion dependencies, which are the theoretical basis for referential integrity on the data. Attempts to solve this problem contain inaccuracy in the statement of the problem and its solution. The errors in formulation of the problem can be associated with the use in the deﬁnition of untyped inclusion dependencies, which leads to permutations of the attributes, although, the attributes in database technology are identiﬁed by name and not by their place. In addition, linking with the use of the inclusion dependencies of heterogeneous attributes, even of the same type, is a sign of lost functional dependencies and leads to interaction of inclusion dependencies and non-trivial functional dependencies. Inaccuracies in the solution of the problem are contained in the statements of axioms and the proof of their properties, including completeness. In this paper we propose an original solution of this problem only for typed inclusion dependencies in the presence of Null values: a new axiom system is proposed, its completeness and soundness are proved. On the basis of inference rules we developed an algorithm for the construction of a not surplus set of typed inclusion dependencies. The correctness of the algorithm is proved.